Ecological and Health Risk Assessments of Trace Elements in Al-Shaibah Dust, Basrah city, Iraq (Journal of University of Babylon for Engineering Sciences, 2018)
This study goals to evaluate the pollution loads of contaminated dust fallen in areas near the oil refinery in Al-Shaibah area and areas around it in Basrah, Iraq between June 2011 and November 2012 in nine stations. Trace elements in dust under study are: (1.chromium Cr, 2.cadmium Cd, 3.nickel Ni and 4.lead Pb). Chronic daily intake CDI for these trace elements through (a.ingestion, b.inhalation and c.dermal contact) is calculated, (the total non-carcinogenic hazard quotient HI) and (the total carcinogenic risk TCR) are calculated. The order of non-carcinogenic hazard quotient for trace elements in dust is: (Cr > Pb > Cd > Ni). Carcinogenic risk order for trace elements in dust is: (Cr > Cd > Pb > Ni), study area is in safe of non-carcinogenic and carcinogenic impact on human health. Finally the ecological risk is evaluated in two indices: integrated pollution level in the environment Cdeg and potential ecological risk RI. The order of RI for trace elements is: (Pb > Cd > Ni > Cr), this study indicates that all stations have low "potential ecological risk".